Effects of adding sodium compounds to corn-rape seed meal type diet on production performance of laying hens - YIN Zhao-zheng; XU AN Shi-rong; PAN Gen-chang (浙江大学学报. 农业与生命科学版)
Adding 0.3% sodium sulphate or 0.3% sodium bicarbonate to corn-rape seed meal type diet with low levels of sulphur-containing amino acid and lysine for ISA brown laying hens, egg laying rate, egg weight and feed efficiency increased, profit per hen also increased obviously, whereas hen mortality was not influenced. When laying hens were fed diet supplemented with sodium bicarbonate, eggshell thickness and strength improved significantly (P<0.05). It was found that addition of sodium sulphate and sodium bicarbonate both in diet was more beneficial to egg laying performance than any single supplement.